Simulasi Pengisian Tangki Cairan dengan Banyak Variabel - Edi Widodo, Catur (BERKALA FISIKA, 2007)
A program for determination of the height of liquid in the container has been done with Python programming language version 4.2. Program was simulated by  position of the height of the liquid dependent on  the time. Program was constuct by mean finite difference equation in object oriented programming Python. Object simulation is container with given radius and infinitif height and has two crane that is liquid enter crane and liquid leaves crane. Input parameter is radius of container, radius of enter crane, radius of leaves crane, and  flow rate of enter crane. Output is  height level of liquid. The result of simulation indicated the terminal velosity is dependent or radius of enter crane, radius of leaves crane, and  flow rate of enter crane